Fabrication and optical properties of Au:SiO2 nanostructured thin films. (December 2019) - Ilkiv, I V; Morozov, K M; Kotlyar, K P; Amelchuk, D.; Bouravleuv, A D
Abstract: We demonstrate synthesis and theoretical study of the optical properties of Au:SiO2 nanocomposite thin films. Localized surface plasmon resonance peak induced by Au NPs was clearly observed in optical spectra at wavelength range between 500 and 600 nm. Intensity and position of PL peak are demonstrated to depend on the Au NPs embedding depth.